Impurity removal and graphite recovery method for aluminum / lithium-containing carbon powder

By using the mixed acid solution and thermal treatment technology, the deepening and recycling of the waste graphite negative powder produced during the production of lithium -ion battery chips can solve the low graphite content and poor electrochemical properties in the existing technologies. The problem has achieved efficient and economical graphite recovery and reuse.

CN119381609AActive Publication Date: 2025-01-28CENT SOUTH UNIV

Patent Information

Application Number
CN202411529592.6
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-10-30
Publication Date
2025-01-28
Estimated Expiration
2044-10-30

AI Technical Summary

Technical Problem

The prior art is difficult to effectively remove metal impurities and organic impurities in waste graphite negative electrode powder generated during the production of lithium-ion battery electrode sheets, resulting in low graphite content and agglomeration of graphite particles, affecting the reversible capacity and electrochemical performance of lithium batteries.

Method used

The leaching agent is used for immersion, including mixed acids of inorganic acid and organic acid soluble in common solvents of water and organic solvents. Based on low temperature oxidation heat treatment and high temperature inert heat treatment, deep deepening and restoration of graphite structure.

Benefits of technology

Achieve the synchronization of metal impurities and organic impurities in the negative powder of waste graphite, which improves the graphite content and graphization degree of recycling graphite, so that recycling graphite can be used directly as the negative electrode material of lithium ion batteries, which significantly improves electrochemical performance Essence

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119381609A_ABST
    Figure CN119381609A_ABST
Patent Text Reader

Abstract

The invention provides an impurity removal and graphite recovery method for aluminum / lithium-containing carbon powder, which comprises the following steps of: leaching waste graphite negative electrode powder containing the aluminum / lithium-containing carbon powder by using a leaching agent to remove impurities, and carrying out solid-liquid separation to obtain preliminarily purified carbon powder; the carbon powder subjected to primary impurity removal is sequentially subjected to low-temperature oxidation heat treatment and high-temperature inert heat treatment, and the recycled graphite is obtained. According to the method, the metal impurities, the binder and the conductive carbon black can be efficiently removed, the recycled and regenerated graphite negative electrode material is low in impurity content and has excellent electrochemical performance, meanwhile, the method has the characteristics of low cost, high efficiency, no secondary pollution and the like, and an economical and effective new method is provided for deep impurity removal and recycling of the aluminum / lithium-containing carbon powder.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of waste electrode material recycling, and relates to a method for removing impurities from aluminum / lithium carbon powder and recovering graphite, and in particular to a method for recovering and reusing waste graphite negative electrode powder containing aluminum / lithium carbon powder. Background Art

[0002] Lithium-ion batteries have the advantages of high energy density and excellent cycle performance, and are widely used in portable electronic products and electric vehicles. Graphite is currently the only commercial negative electrode material due to its high stability and excellent conductivity. In the process of preparing graphite negative electrode sheets, coating, rolling and slitting will inevitably produce defective products, and further separation of active substances will obtain waste graphite negative electrode powder containing aluminum / lithium carbon powder.

[0003] Waste graphite negative electrode powder is mixed with binders and conductive carbon black as well as metal impurities collected during the collection process. Literature research shows that the reduction potential of metal ions is lower than that of lithium ions. Therefore, during the charging process, metal ions will first be embedded in the graphite negative electrode and occupy lithium storage sites, which will reduce the sites where lithium ions can be embedded, resulting in a reduction in the reversible capacity of the lithium battery. In addition, the binder and conductive carbon black attached to the surface of the waste graphite negative electrode carbon powder will cause serious graphite agglomeration, thereby affecting granulation, and will also reduce the amount of active substances, thereby affecting the capacity of the graphite negative electrode. Based on the above analysis, due to the presence of impurities, the graphite content in the waste graphite negative electrode powder is low, which will affect the capacity of the graphite negative electrode and cause the agglomeration of graphite particles.

[0004] The Chinese patent document of publication number CN 116143115 A discloses a method for recycling carbon negative electrode scraps, which adopts a treatment method of subcritical combined flotation assisted by dibenzoyl peroxide, wherein dibenzoyl peroxide assisted subcritical treatment can surface treat each component in the scraps, realize the dissociation of each component, amplify the physicochemical differences between the components, further cooperate with flotation and the combined control of reagents, especially collectors and inhibitors, and realize the effective separation and utilization of graphite and conductive agents and binders. However, this patent is only aimed at separating organic impurities in graphite, but it is impossible to effectively remove metal impurities. In addition, high temperature method and hydrofluoric acid method are mainly used in industry to recycle waste graphite materials. In order to improve the purity of graphite, graphite deep processing enterprises often use hydrofluoric acid method to remove metal impurities, but hydrofluoric acid is highly toxic and corrosive, and has high requirements for equipment and environmental protection.

[0005] At present, the methods for removing impurities or recycling graphite mainly focus on graphite raw materials and recycling graphite negative electrode materials from waste batteries. However, there is little research on waste graphite negative electrode powder in the production process due to its high recycling cost. Therefore, how to efficiently remove impurities and recycle graphite from waste graphite negative electrode powder through simple methods and realize reuse is an urgent problem to be solved in this field. Summary of the invention

[0006] In view of the problem that the prior art lacks a method for universal deep impurity removal and efficient recycling of waste graphite negative electrode powder containing aluminum / lithium carbon powder in the production process of lithium-ion battery pole pieces, the object of the present invention is to provide a method for removing impurities and recovering graphite containing aluminum / lithium carbon powder, which can simultaneously remove metal impurities and organic impurities, and the recovered graphite has a high content and a good degree of graphitization, and can be directly used as a negative electrode material for lithium-ion batteries.

[0007] In order to achieve the above technical objectives, the present invention provides a method for removing impurities from aluminum / lithium carbon powder and recovering graphite, the method comprising: using a leaching agent to remove impurities from waste graphite negative electrode powder containing aluminum / lithium carbon powder, and performing solid-liquid separation to obtain carbon powder with preliminary impurities removed; the carbon powder with preliminary impurities removed is subjected to low-temperature oxidation heat treatment and high-temperature inert heat treatment in sequence to obtain recovered graphite; the leaching agent is obtained by dissolving a mixed acid of an inorganic acid and an organic acid in a co-solvent composed of water and an organic solvent.

[0008] The key to the technical solution of the present invention is to use a special leaching agent to remove metal impurities, conductive agents and binder components in the waste graphite negative electrode powder containing aluminum / lithium carbon powder, and combine the process of continuous low-temperature-high-temperature heat treatment to deeply remove impurities and restore the graphite structure. Specifically, the inorganic acid used in the leaching agent can react with the metal impurities in the waste graphite negative electrode powder to form a soluble salt, and the presence of the organic acid can play the role of a reducing agent, converting the soluble salt formed by the high-valent metal ions into a soluble salt formed by the low-valent metal ions with higher solubility, and further filtering and separating to remove the metal impurities in the graphite, so the interaction of the mixed acid can improve the removal effect of metal impurities, especially the removal effect of aluminum and lithium metal impurities. At the same time, the aqueous solution in the co-solvent can dissolve the aqueous adhesive in part of the raw material; in addition, there is a mutual attraction between the structure of the oily adhesive molecule and the organic solvent molecule, and the van der Waals force between the organic solvent molecules can promote the migration of the oily adhesive molecule into the solution, and the oily adhesive can be dissolved in the organic solvent under heating conditions. Therefore, the metal impurities and most of the adhesive can be removed by leaching. Low-temperature oxidation heat treatment can further decompose the conductive carbon black and binder, causing them to be discharged in the form of gas, thereby achieving the purpose of deep impurity removal; finally, high-temperature inert heat treatment can repair the graphite structure and increase the degree of graphitization.

[0009] The process of the present invention cannot be changed at will. If low-temperature oxidation treatment is performed first and then acid leaching is performed, the aluminum element in the raw material is easily converted into aluminum oxide through low-temperature oxidation treatment, and aluminum oxide hardly reacts with acid, thereby significantly reducing the aluminum removal rate.

[0010] At the same time, the inventors found that when there is only inorganic acid in the mixed acid, the leaching rate of some metal impurities is not high; and when there is only organic acid in the mixed acid, since the organic acid is a weak acid, a large amount of organic acid needs to be consumed or a higher concentration of organic acid is required. Therefore, the use of organic acid alone is not economical, and it cannot cooperate with inorganic acid to improve the removal rate of metal impurities. When there is only water in the co-solvent, water cannot react with metal impurities to generate soluble salts through reduction reaction to separate from graphite solids, and the oily binder molecules cannot be dissolved, and the removal effect of metal impurities and oily binders will be significantly reduced.

[0011] As a preferred solution, the impurities contained in the waste graphite negative electrode powder containing aluminum / lithium carbon powder include metal impurities, binders and conductive carbon black. The total content of the binder and the conductive carbon black is 1% to 3wt%. The types of binders include styrene-butadiene rubber, carboxymethyl cellulose and polyvinylidene fluoride. The metal impurities are mainly Li, Al, Cu, Ni, Co, Mn and Fe, and the total content of the metal impurities is 1.4 to 1.6wt%.

[0012] As a preferred solution, the inorganic acid is at least one of sulfuric acid, hydrochloric acid and nitric acid.

[0013] As a preferred embodiment, the organic acid is at least one of citric acid, acetic acid, malic acid, maleic acid, formic acid and ascorbic acid.

[0014] As a preferred embodiment, the organic solvent is at least one of dichloromethane, tetrahydrofuran (THF), N,N-dimethylformamide (DMF), N-methylpyrrolidone (NMP), dimethyl sulfoxide (DMSO) and N,N-dimethylacetamide (DMAC).

[0015] As a preferred solution, the molar ratio of the inorganic acid to the organic acid is (5-50):1; the volume ratio of the water to the organic solvent is (30-100):1. The molar ratio of the four components in the leaching agent of the present invention has a direct impact on the leaching and impurity removal effect. If the molar ratio of the inorganic acid to the organic acid is too small, more mixed acid will be consumed. If the ratio is too large, the high-valent metal ions will not be completely reduced due to the reduced content of the organic acid as a reducing agent, resulting in a low metal impurity removal rate. If the volume ratio of water to organic solvent is too low, too much organic solvent will remain in the graphite, reducing the purity of the graphite. If it is too high, the organic solvent will not be able to completely dissolve the binder.

[0016] As a preferred solution, the conditions for leaching and impurity removal are: temperature of 10-90°C, total concentration of leaching agent of 0.1-7 mol / L, liquid-solid ratio of leaching agent to waste graphite negative electrode powder containing aluminum / lithium carbon powder of 5-50 mL / g, and time of 0.5-6 h. During leaching and impurity removal, the present invention can promote the dissolution of the oily binder in the organic solvent for removal under heating, and the temperature is further preferably 50-90°C. When the liquid-solid ratio of the leaching agent decreases, the volume of liquid in contact with the solid material decreases, resulting in a decrease in mass transfer efficiency, thereby reducing the removal effect of metal impurities, and the liquid-solid ratio is further preferably 10-20 mL / g.

[0017] As a preferred solution, the leaching and impurity removal is promoted by at least one of magnetic stirring, mechanical stirring or ultrasonic stirring, and the stirring time is 0.5 to 3 hours. When mechanical stirring or magnetic stirring is used, the speed is 100 to 1500 rmin -1 .

[0018] As a preferred solution, the conditions of the low-temperature oxidation heat treatment are: temperature of 300-600°C, holding time of 1-5h, heating rate of 1-10°C / min, air and / or oxygen atmosphere, more preferably oxygen atmosphere. The present invention can decompose the conductive carbon black and the binder by heat treatment in an oxidizing atmosphere and remove them in the form of gases such as CO2 and H2O(g).

[0019] As a preferred solution, the conditions of the high-temperature inert heat treatment are: temperature of 800-1600°C, holding time of 4-10h, heating rate of 1-10°C / min, and argon and / or nitrogen atmosphere. The present invention can accelerate the movement of carbon atoms through high-temperature inert heat treatment, promote the transformation of amorphous carbon to graphite structure, help the growth and arrangement of graphite crystallites, and reduce structural defects in graphite materials, thereby improving the degree of graphitization. Graphite will oxidize and decompose into CO2 at too high a temperature under air or oxygen conditions, so the heat treatment temperature should be controlled to be above the decomposition temperature of organic impurities and below the decomposition temperature of graphite. The higher the temperature of the high-temperature inert treatment, the better the degree of graphitization, but there is no need for too high a treatment temperature, as long as the degree of graphitization reaches the commercial graphite standard.

[0020] As a preferred solution, the graphite content in the recovered graphite is above 99wt%. The content of metal impurities and organic impurities in the graphite recovered after impurity removal by the method of the present invention is significantly reduced.

[0021] The present invention provides a method for removing impurities and recovering graphite from aluminum / lithium-containing carbon powder, the method comprising the following steps:

[0022] S1. dissolving a mixed acid of an inorganic acid and an organic acid in a molar ratio of (50-5):1 in a co-solvent composed of water and an organic solvent in a volume ratio of (100-30):1 to obtain a leaching agent, and then mixing the leaching agent with the waste graphite negative electrode powder containing aluminum / lithium carbon powder and stirring at a temperature of 10-90° C.;

[0023] S2: the mixed solution obtained in step S1 is washed with pure water to separate the solid from the liquid, and the washed solid is dried at a temperature of 50 to 90° C. for a drying time of 5 to 18 hours;

[0024] S3: The solid obtained in step S2 is subjected to continuous low-temperature-high-temperature heat treatment, that is, firstly heat treated in a low-temperature oxidizing atmosphere, and then heat treated in a high-temperature inert atmosphere, to finally obtain recovered graphite.

[0025] As a preferred solution, the solid-liquid separation method in step S2 includes suction filtration, normal pressure filtration and centrifugation, and the filtrate / supernatant after filtration is neutral.

[0026] The regenerated graphite electrode material is used as a negative electrode material for lithium-ion batteries for electrochemical testing to evaluate its electrochemical performance. The specific steps are as follows: the recycled graphite, acetylene black, and polyvinylidene fluoride (PVDF) obtained after removing impurities from the above-mentioned waste graphite negative electrode powder containing aluminum / lithium carbon powder are evenly mixed in N-methylpyrrolidone (NMP) to form a slurry, which is ground and coated on a copper foil, and dried in an oven to obtain a negative electrode sheet.

[0027] As a preferred solution, the mass ratio of the graphite material obtained after removing impurities from the waste graphite negative electrode powder in the slurry composition, acetylene black, and polyvinylidene fluoride (PVDF) is 8:1:1.

[0028] As a preferred solution, the stirring rate of the mixed slurry is 100 to 1500 r / min, and the stirring time is 1 to 24 hours, so that the slurry is fully mixed and uniform.

[0029] As a preferred solution, the electrode requires a drying temperature of 50 to 90° C. and a drying time of 5 to 18 hours, to ensure that the electrode surface is dry and flat after drying, and that the active material is firmly bonded to the copper foil.

[0030] As a preferred solution, the lithium salt in the electrolyte is 1 mol / L of one of lithium hexafluorophosphate (LiPF6), lithium tetrafluoroborate (LiBF4), lithium perchlorate (LiClO4), etc., and the solvent is a mixed solvent of two or more of ethylene carbonate (EC), diethyl carbonate (DEC), methyl vinyl carbonate (EMC), propylene carbonate (PC) and dimethyl carbonate (DMC).

[0031] Compared with the prior art, the present invention has the following beneficial effects:

[0032] 1) The method of the present invention can simultaneously remove metal impurities and organic impurities (conductive agent and binder) in waste graphite negative electrode powder containing aluminum / lithium carbon powder, and the recovered graphite has a high content and a good degree of graphitization, and can be directly used as a negative electrode material for lithium ion batteries.

[0033] 2) The content of most metal elements in the recycled graphite of the present invention is below 5ppm, and the binder and conductive carbon black are also well removed. In the electrochemical performance test, for example, the maximum specific capacity of the graphite electrode material after impurity removal and recycling can reach 368.2mAh g -1 Significantly better than the 330.3mAh g of waste graphite negative electrode powder -1 In the subsequent cycle performance test, at a current density of 0.5C, the specific capacity of the recycled graphite electrode material after 100 cycles still reached 357.1 mAh g -1 , while the specific capacity of the waste graphite negative electrode powder is only 265.9 mAh g -1 .

[0034] 3) The present invention has the characteristics of low cost, high efficiency and no secondary pollution, and provides a new economical and effective way for the recovery and recycling of waste graphite negative electrode powder containing aluminum / lithium carbon powder. BRIEF DESCRIPTION OF THE DRAWINGS

[0035] Figure 1 The present invention is a schematic diagram of a method for removing impurities from aluminum / lithium-containing carbon powder and recovering graphite.

[0036] Figure 2 This is a scanning electron microscope image of recycled graphite. Figure 2 It can be seen that the surface of the recycled graphite is smooth and there are no obvious impurities attached to its surface. DETAILED DESCRIPTION

[0037] In order to make the purpose, technical solution and features of the present invention more clearly understood, the present invention is further described in detail below in conjunction with the accompanying drawings and embodiments. It should be understood that the specific embodiments described herein are only used to explain the present invention and are not intended to limit the present invention.

[0038] The contents of various inorganic impurities in the waste graphite negative electrode powder containing aluminum / lithium carbon powder (hereinafter referred to as waste graphite negative electrode powder) used in the embodiments of the present invention and the comparative examples are shown in Table 1, wherein the total content of the binder and the conductive carbon black is 1.5wt%, and the total content of metal impurities is 1.5wt%.

[0039] Table 1 Inorganic impurity content of aluminum / lithium carbon powder

[0040]

[0041] Example 1

[0042] S1. A mixed acid of hydrochloric acid and citric acid in a molar ratio of 49:1 was dissolved in a co-solvent consisting of water and dimethyl sulfoxide (DMSO) in a volume ratio of 100:1, and magnetic stirring was performed for 0.5 h to obtain a leaching agent, wherein the concentration of the leaching agent was 1 mol L -1 , keep the liquid-solid ratio of leaching agent to waste graphite negative electrode powder at 5:1mL g -1 The leaching temperature was 50 °C, the leaching time was 4 h, and the stirring rate was controlled at 500 rmin. -1 ;

[0043] S2, filtering the mixed solution after the reaction in step S1 to separate the solid from the liquid, and washing the solid with pure water to ensure that the pH of the final filtrate is 7, and then drying the filtered solid at 60° C. for 12 hours;

[0044] S3, drying the solid obtained in step S2 in an air atmosphere at 10°C min -1 The temperature was raised to 500 °C at a heating rate of 1.5 °C and kept at this temperature for 3 h. The temperature was then heated at 8 °C min -1 The recovered graphite was obtained by increasing the temperature to 1000°C at a heating rate and keeping the temperature for 5 hours.

[0045] ICP was used to analyze the metal impurity content in the recovered graphite. The test results are shown in Table 2 below.

[0046] Table 2 Recycled graphite ICP test results

[0047]

[0048] Further thermogravimetric analysis results show that the graphite content is 99.5wt.%. The graphite content after thermogravimetric analysis can reflect the removal effect of organic impurities in the material. The higher the graphite content, the more thorough the removal of organic impurities.

[0049] Example 2

[0050] S1. A mixed acid of sulfuric acid and acetic acid in a molar ratio of 49:1 was dissolved in a co-solvent consisting of water and N,N-dimethylformamide (DMF) in a volume ratio of 100:1, and mechanically stirred for 1 h to obtain a leaching agent, wherein the concentration of the leaching agent was 5 mol L -1 , keep the liquid-solid ratio of leaching agent to waste graphite negative electrode powder at 10:1mL g -1 The leaching temperature was 90 °C, the leaching time was 3 h, and the stirring rate was maintained at 500 rmin. -1 ;

[0051] S2, filtering the mixed solution after the reaction in step S1 to separate the solid from the liquid, and washing the solid with pure water to ensure that the pH of the final filtrate is 7, and then drying the filtered solid at 80° C. for 12 hours;

[0052] S3, drying the solid obtained in step S2 in an oxygen atmosphere at 10°C min -1 The temperature was raised to 350 °C at a heating rate of 1.5 °C / min and kept at this temperature for 2 h. -1 The recovered graphite was obtained by increasing the temperature to 1600°C at a heating rate and keeping the temperature for 7h.

[0053] ICP was used to analyze the metal impurity content in the recovered graphite. The test results are shown in Table 3 below.

[0054] Table 3 Recycled graphite ICP test results

[0055]

[0056] Further thermogravimetric analysis results showed that the graphite content was 99.89wt.%.

[0057] Example 3

[0058] S1. A mixed acid of sulfuric acid and maleic acid in a molar ratio of 44:1 was dissolved in a co-solvent consisting of water and tetrahydrofuran (THF) in a volume ratio of 79:1, and ultrasonically stirred for 0.5 h to obtain a leaching agent, wherein the concentration of the leaching agent was 1.5 mol L -1 , keep the liquid-solid ratio of leaching agent to waste graphite negative electrode powder at 50:1mL g -1 The leaching temperature was 60 °C, the leaching time was 5 h, and the stirring rate was controlled at 1500 rmin. -1 ;

[0059] S2, filtering the mixed solution after the reaction in step S1 to separate the solid from the liquid, and washing the solid with pure water to ensure that the pH of the final filtrate is 7, and then drying the filtered solid at 50° C. for 10 hours;

[0060] S3, drying the solid obtained in step S2 in an air atmosphere at 8°C min -1 The temperature was raised to 550 °C at a heating rate of 10 °C min-1 and kept at this temperature for 2 h. -1 The recovered graphite was obtained under the conditions of increasing the temperature to 800°C at a heating rate and keeping the temperature for 5h.

[0061] ICP was used to analyze the metal impurity content in the recovered graphite. The test results are shown in Table 4 below.

[0062] Table 4 Recycled graphite ICP test results

[0063]

[0064] Further thermogravimetric analysis results showed that the graphite content was 99.02wt.%.

[0065] Example 4

[0066] S1. Dissolve a mixed acid of nitric acid and ascorbic acid in a molar ratio of 39:1 in a co-solvent of water and dichloromethane in a volume ratio of 99:1, and stir magnetically for 1.5 h to obtain a leaching agent, wherein the concentration of the leaching agent is 3.5 mol L -1 , keep the liquid-solid ratio of leaching agent to waste graphite negative electrode powder at 10:1mL g -1 The leaching temperature was 10 °C, the leaching time was 3 h, and the stirring rate was controlled at 1500 rmin. -1 ;

[0067] S2, filtering the mixed solution after the reaction in step S1 to separate the solid from the liquid, and washing the solid with pure water to ensure that the pH of the final filtrate is 7, and then drying the filtered solid at 80° C. for 10 hours;

[0068] S3, drying the solid obtained in step S2 in an oxygen atmosphere at 3°C ​​min -1 The temperature was raised to 350 °C at a heating rate of 10 °C min-1 and kept at this temperature for 4 h. -1 The recovered graphite was obtained by increasing the temperature to 1000°C at a heating rate and keeping the temperature for 4 hours.

[0069] ICP was used to analyze the metal impurity content in the recovered graphite. The test results are shown in Table 5 below.

[0070] Table 5 Recycled graphite ICP test results

[0071]

[0072] Further thermogravimetric analysis results showed that the graphite content was 99.32wt.%.

[0073] Example 5

[0074] This embodiment is basically the same as embodiment 2, except that the liquid-solid ratio of the volume of the leaching agent to the waste graphite negative electrode powder in step S1 is 10:1 mL g -1 Reduced to 5:1mL g -1 .

[0075] ICP was used to analyze the metal impurity content in the recovered graphite. The test results are shown in Table 6 below.

[0076] Table 6 Recycled graphite ICP test results

[0077]

[0078] Further thermogravimetric analysis results showed that the graphite content was 99.50wt.%.

[0079] Comparative Example 1

[0080] This comparative example is basically the same as Example 1, except that the leaching agent in step S1 is pure water.

[0081] ICP was used to analyze the metal impurity content in the recovered graphite. The test results are shown in Table 7 below.

[0082] Table 7 Recycled graphite ICP test results

[0083]

[0084] Further thermogravimetric analysis results showed that the graphite content was 92.87wt.%.

[0085] Comparative Example 2

[0086] This comparative example is basically the same as Example 1, except that in step S3, the heat treatment is directly carried out under an inert atmosphere at a temperature of 1000° C. to obtain recovered graphite.

[0087] ICP was used to analyze the metal impurity content in the recovered graphite. The test results are shown in Table 8 below.

[0088] Table 8 Recycled graphite ICP test results

[0089]

[0090] Further thermogravimetric analysis results showed that the graphite content was 97.5wt.%.

[0091] Comparative Example 3

[0092] This comparative example is basically the same as Example 2, except that the leaching agent in step S1 is a mixed acid aqueous solution of sulfuric acid and acetic acid in a molar ratio of 49:1 (without organic solvent).

[0093] ICP was used to analyze the metal impurity content in the recovered graphite. The test results are shown in Table 9 below.

[0094] Table 9 Recycled graphite ICP test results

[0095]

[0096] Further thermogravimetric analysis results showed that the graphite content was 97.89wt.%.

[0097] Comparative Example 4

[0098] This comparative example is substantially the same as Example 3, except that in step S1, only sulfuric acid is used as the acid solution.

[0099] ICP was used to analyze the metal impurity content in the recovered graphite. The test results are shown in Table 10 below.

[0100] Table 10 Recycled graphite ICP test results

[0101]

[0102] Further thermogravimetric analysis results showed that the graphite content was 93.06wt.%.

[0103] Comparative Example 5

[0104] This comparative example is basically the same as Example 3, except that, after the air heat treatment in step S3, there is no need to perform subsequent heat treatment under an inert atmosphere to directly obtain the recovered graphite.

[0105] ICP was used to analyze the metal impurity content in the recovered graphite. The test results are shown in Table 11 below.

[0106] Table 11 Recycled graphite ICP test results

[0107]

[0108] Further thermogravimetric analysis results showed that the graphite content was 97.54wt.%.

[0109] Comparative Example 6

[0110] This comparative example is basically the same as Example 4, except that the acid solution in step S1 is only nitric acid.

[0111] ICP was used to analyze the metal impurity content in the recovered graphite. The test results are shown in Table 12 below.

[0112] Table 12 Recycled graphite ICP test results

[0113]

[0114] Further thermogravimetric analysis results showed that the graphite content was 96.78wt.%.

[0115] Comparative Example 7

[0116] This comparative example is basically the same as Example 4, except that the acid solution in step S1 is only ascorbic acid.

[0117] ICP was used to analyze the metal impurity content in the recovered graphite. The test results are shown in Table 13 below.

[0118] Table 13 Recycled graphite ICP test results

[0119]

[0120] Further thermogravimetric analysis results showed that the graphite content was 97.63wt.%.

[0121] Electrochemical performance test

[0122] The recycled graphite negative electrode material obtained in the above examples 1 to 5 and comparative examples 1 to 7 and the waste graphite negative electrode powder were made into electrode slurry, and the slurry ratio was active material: binder (PVDF): conductive agent (acetylene black) = 8:1:1. The slurry was evenly stirred and coated on copper foil, and then dried in an oven. The dried electrode sheet was cut and used as the working electrode of the button battery; the lithium sheet was used as the counter electrode; the lithium salt in the electrolyte selected 1 mol / L lithium hexafluorophosphate (LiPF6), and the solvent selected a mixed solvent of ethylene carbonate (EC), diethyl carbonate (DEC) and methyl ethylene carbonate (EMC) and the volume ratio of the three solvents was 1:1:1, and the above materials were assembled into a half-cell. The half-cells assembled with different materials were tested using the blue electric system, and the charge and discharge voltage range was 0.005 to 3V. The current density used for the first charge and discharge cycle experiment was 0.1C, and the first charge and discharge coulomb efficiency of the battery was tested at this current density; the current density used for the long cycle test was 0.5C.

[0123] According to the above scheme, the stirring rate required for the mixed slurry is 1500rmin -1 , stirring time 10h, so that the slurry is fully mixed;

[0124] According to the above scheme, the required drying temperature of the electrode is 80°C and the drying time is 12h, which ensures that the surface of the electrode is dry and flat after drying, and the active material is firmly bonded to the copper foil.

[0125] The test results are shown in Table 14 below.

[0126] Table 14 Electrochemical test results of different electrode materials

[0127]

[0128]

[0129] The first cycle discharge specific capacity (mAh g -1) and the capacity retention rate after 100 cycles show that Example 3 improves the degree of graphitization of the material after heat treatment in an inert atmosphere, so the electrochemical performance is higher.

Claims

1. A method for removing impurities and recovering graphite from aluminum / lithium-containing carbon powder, characterized in that: The waste graphite negative electrode powder containing aluminum / lithium carbon powder is leached and removed by a leaching agent, and solid-liquid separation is performed to obtain carbon powder with preliminary impurities removed; the carbon powder with preliminary impurities removed is sequentially subjected to low-temperature oxidation heat treatment and high-temperature inert heat treatment to obtain recovered graphite; The leaching agent is obtained by dissolving a mixed acid of an inorganic acid and an organic acid in a co-solvent composed of water and an organic solvent.

2. The method for removing impurities and recovering graphite from aluminum / lithium-containing carbon powder according to claim 1, characterized in that: The inorganic acid is at least one of sulfuric acid, hydrochloric acid and nitric acid; the organic acid is at least one of citric acid, acetic acid, malic acid, maleic acid, formic acid and ascorbic acid.

3. The method for removing impurities and recovering graphite from aluminum / lithium-containing carbon powder according to claim 2, characterized in that: The organic solvent is at least one of dichloromethane, tetrahydrofuran, N,N-dimethylformamide, N-methylpyrrolidone, dimethyl sulfoxide and N,N-dimethylacetamide.

4. The method for removing impurities and recovering graphite from aluminum / lithium-containing carbon powder according to any one of claims 1 to 3, characterized in that: The molar ratio of the inorganic acid to the organic acid is (5-50):1; the volume ratio of the water to the organic solvent is (30-100):

1.

5. The method for removing impurities and recovering graphite from aluminum / lithium-containing carbon powder according to claim 4, characterized in that: The conditions for leaching and impurity removal are: temperature of 10-90° C., total concentration of leaching agent of 0.1-7 mol / L, liquid-solid ratio of leaching agent to waste graphite negative electrode powder containing aluminum / lithium carbon powder of 5-50 mL / g, and time of 0.5-6 h.

6. The method for removing impurities and recovering graphite from aluminum / lithium-containing carbon powder according to claim 5, characterized in that: The leaching and impurity removal adopts at least one of magnetic stirring, mechanical stirring or ultrasonic stirring to promote leaching, and the stirring time is 0.5 to 3 hours.

7. A method for removing impurities and recovering graphite from aluminum / lithium-containing carbon powder according to claim 1, 4 or 5, characterized in that: The conditions of the low-temperature oxidation heat treatment are: temperature of 300-600° C., holding time of 1-5 hours, heating rate of 1-10° C. / min, and air and / or oxygen atmosphere.

8. The method for removing impurities and recovering graphite from aluminum / lithium-containing carbon powder according to claim 7, characterized in that: The conditions of the high-temperature inert heat treatment are: temperature of 800-1600° C., holding time of 4-10 hours, heating rate of 1-10° C. / min, and argon and / or nitrogen atmosphere.

9. The method for removing impurities and recovering graphite from aluminum / lithium-containing carbon powder according to claim 1, characterized in that: The graphite content in the recovered graphite is above 99wt%.

Citation Information

Patent Citations

  • Recycling method for leftover materials of carbon negative electrode

    CN116143115A

  • Method for preparing graphene through waste lithium batteries

    CN102868006A

  • Recycling method for waste lithium ion battery negative electrode material

    CN107887666A

  • Method for regenerating waste lithium ion battery graphite negative electrode material

    CN112670605A

  • Comprehensive recycling and resource utilization method for aluminum electrolysis waste cathode carbon blocks and application of comprehensive recycling and resource utilization method

    CN115156238A

Cited By

  • Method for preparing recycled graphite material from waste graphite saggar, negative electrode material and lithium ion battery

    CN121085263A